2001
DOI: 10.1021/ja011195t
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Spectra and Molecular Structures of (Z)-Pent-2-en-4-ynenitrile and Maleonitrile

Abstract: Accurate equilibrium structures have been determined for (Z)-pent-2-en-4-ynenitrile (8) and maleonitrile (9) by combining microwave spectroscopy data and ab initio quantum chemistry calculations. The microwave spectra of 10 isotopomers of 8 and 5 isotopomers of 9 were obtained using a pulsed nozzle Fourier transform microwave spectrometer. The ground-state rotational constants were adjusted for vibration-rotation interaction effects calculated from force fields obtained from ab initio calculations. The resulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 87 publications
(138 reference statements)
0
34
0
Order By: Relevance
“…[25]. [1,7,19] Similar to the situation of 1R, both 2R t (2R in the T 1 state) and 3R t (3R in the T 1 state) have lower symmetry (C 1 symmetry) than their respective S 0 states. The CASPT2 geometry of 2R s is in good agreement with experiment (see Fig.…”
Section: Bergman Cyclizations Of 2r and 3rmentioning
confidence: 93%
See 4 more Smart Citations
“…[25]. [1,7,19] Similar to the situation of 1R, both 2R t (2R in the T 1 state) and 3R t (3R in the T 1 state) have lower symmetry (C 1 symmetry) than their respective S 0 states. The CASPT2 geometry of 2R s is in good agreement with experiment (see Fig.…”
Section: Bergman Cyclizations Of 2r and 3rmentioning
confidence: 93%
“…Halter et al [1] performed the geometry optimization calculations for 2R and 4R in their ground states (the S 0 states) using CCSD(T)/cc-pVTZ method and the optimized geometries are in agreement with experiment. For the Bergman cyclizations of 2R and 3R (reactions 2 and 3 in Scheme 1), there are a few theoretical studies [1,7,19,22,[36][37][38] reported in the literature.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations